Endemism of Crimean flora in landscape context (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Distribution of narrow endemics in Crimean landscapes is elucidated with revealing of some plant geographical features.
Keywords: the Crimea, flora, endemic, landscape.